Interaction of phosphorus and GA3 improved oilseed flax grain yield and phosphorus-utilization efficiency - Wang, Yingze; Cao, Zhi; Gao, Yuhong; Wu, Bing; Niu, Junyi; Yan, Bin; Wang, Yifan; Cui, Zhengjun; Wen, Ming; Xu, Peng; Wang, Haidi; Ma, Xingkang (Frontiers in Plant Science, 2024)
Introduction Phosphorus nutrition and hormone concentration both affect crop yield formation. Ascertaining the interaction of phosphorus and GA3 has a synergistic effect on the grain yield and phosphorus utilization efficiency of oilseed flax in dryland. It is extremely important for improving grain yield and phosphorus utilization efficiency. Methods A field experiment was conducted in 2019 and 2020 at the Dingxi Oil Crops Test Station to investigated the effects of phosphorus, gibberellin (GA3), and their interaction on the grain yield and phosphorus-utilization efficiency of oilseed flax plants. Phosphorus fertilizer was applied at three levels (0, 67.5, 135 kg P2O5·ha-1) and GA3 was also sprayed at three concentrations (0, 15, and 30 mg·L-1). Results The results showed that application of 67.5 kg P2O5·ha-1 reduced leaves acid phosphatase (ACPase) activity, but increased phosphorus accumulation throughout the growth period, the 1000-kernel weight (TKW), and the number of grains per capsule. Spraying GA3 significantly increased the leaves ACPase activity, phosphorus accumulation after anthesis and its contribution to grain, phosphorus-utilization efficiency, the number of capsules per plant, and TKW. The phosphorus accumulation at the anthesis, kernel, and maturity stages under the treatment of fertilizing 67.5 kg P2O5·ha-1 and spraying 30 mg·L-1 GA3 were increased by 56.06%, 73.51%, and 62.17%, respectively, compared with the control (no phosphorus, no GA3). And the phosphorus accumulation after anthesis and its contribution to grain also increased. 67.5 kg P2O5·ha-1 combined with 30 mg·L-1 GA3 and 135 kg P2O5·ha-1 combined with 15 mg·L-1 GA3 both significantly increased grain yield of oilseed flax, reaching 1696 kg·ha-1 and 1716 kg·ha-1 across two years, respectively. And there was no significant difference between them. However, the former treatment significant increased the apparent utilization rate, agronomic utilization rate, and partial productivity of phosphorus. The interaction between phosphorus and GA3 was significant for grain yield. Conclusion Therefore, the application of 67.5 kg P2O5·ha-1 in combination with 30 mg·L-1 GA3 is an effective fertilization approach for enhancing oilseed flax growth and grain yield in the experiment region and other similar areas.